2021
DOI: 10.5603/gp.a2021.0229
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte related peptides — galanin and resistin in endometrioid type endometrium cancer

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Ginekologia Polska" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Based on these results, we could hypothesize that the decreased resistin level in BBD may be a biochemical marker of metabolic alterations related to the development of BC and other neoplasms such as epithelial ovarian cancer, endometrial cancer, and esophageal squamous cell carcinoma [29][30][31].…”
Section: Discussionmentioning
confidence: 94%
“…Based on these results, we could hypothesize that the decreased resistin level in BBD may be a biochemical marker of metabolic alterations related to the development of BC and other neoplasms such as epithelial ovarian cancer, endometrial cancer, and esophageal squamous cell carcinoma [29][30][31].…”
Section: Discussionmentioning
confidence: 94%
“…The latest available studies show that elevated resistin levels correlate with endometrial cancer stimulation, development and invasion, which is associated with advanced cancer stage and a worse prognosis for the patient [ 41 , 173 , 178 , 187 , 188 ]. Nergiz Avcıoğlu et al [ 189 ] reported that resistin levels >0.27 ng/mL increased the risk of endometrial cancer by as much as 5.6 times. The pathomechanism of endometrial cancer development is associated with the activation of multiple signaling pathways, mainly the MAP kinase pathway, resulting in increased synthesis of P-selectin and fractalkine in endothelial cells [ 41 , 187 , 190 ].…”
Section: Resistinmentioning
confidence: 99%